The role of liver fluke invasion in the pathogenesis of cholangiocarcinoma - Bykowska-Tumasz, Martyna; Sikorska, Katarzyna (Clinical and Experimental Hepatology, 2026)
Infections with the liver flukes Clonorchis sinensis and Opisthorchis viverrini are currently endemic in Southeast and East Asia. Their limited ecological and geographical distribution is caused by environmental factors and culinary habits of the human population. Climate change, globalization, increasing human mobility, and environmental changes affecting the reservoir of zoonotic infections may change the epidemiology of trematodes. The species C. sinensis and O. viverrini have been recognized as biological carcinogens leading to the development of biliary tract cancer. This paper presents the epidemiology of infections with the above species, and summarizes the known mechanisms of cholangiocarcinogenesis induced by parasitic invasion.